Sistem Informasi Aplikasi Penyusunan Sasaran Kerja Pegawai (SKP) pada Kanwil Kementerian Hukum dan Ham Aceh - Yulita Ananda (KITA Institute, 2020)
The design of the Information Systems Application System for Employee Work Target Compilation (SKP) is based on the method of evaluating civil servant work performance systematically combining the Civil Service Employee Work Target assessment with work behavior assessment. Performance appraisal consists of two elements, namely SKP and Work Behavior, with an assessment weighting of SKP elements at 60% and work behavior at 40%. From the depiction of the service mechanism at the KEMKUMHAM Aceh, an integrated information system is needed to assemble the existing subsystems into a mutually supportive unit given the still not optimal role of the computerized system in the existing service mechanism. The purpose of this study was to design an Information System for Employee Job Target Compilation (SKP) Application at the Regional Office of the Ministry of Law and Ham Aceh using Visual BASIC.NET. The design of the system used by the Rapid Application Development (RAD) method, a software development process model classified as incremental (multilevel) techniques. RAD emphasizes short, short, and fast development cycles, and data collection techniques using research methods by observation, interview, and literature study. The tools used are Microsoft Visual Basic .NET as an application in interface design and Microsoft Office Access as a DBMS. The test results of this application are the systems that are built already meet the needs, the input data process has met the needs and the resulting report has met the needs.